Numerical study on shear strengthening of reinforced concrete (RC) deep beams with and without stirrups using near-surface mounted FRP bars - Shadhar, Mohanad Hatem (2020)
Near surface mounted (NSM) technique is an emerging technique for increasing the strength of reinforced concrete (RC) members. It is applied to strengthen or repair RC members. Fibre reinforced polymers (FRP) bars are commonly used through the NSM technique to strengthen RC members. However, limited studies on NSM strengthening using FRP bars on RC deep beams are available. In this research, a numerical investigation was carried out on RC deep beams strengthened in shear with NSM-FRP bars using the ABAQUS